2019
DOI: 10.1002/mgg3.585
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenIL‐4tagging single nucleotide polymorphisms and the risk of lung cancer in China

Abstract: Background In China, lung cancer is also the most commonly diagnosed cancer with a lower 5‐year survival rate, leading to high social burdens. Recently, many studies highlighted the importance of inflammation in the initiation and progression of cancer. The goal of this study was to investigate the association between interleukin‐4 (IL‐4, OMIM#147780) single nucleotide polymorphisms (SNPs) and lung cancer susceptibility. Methods A case‐control study was conducted in a Chinese population including 199 male pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Moreover, IL-4 polymorphisms have been found linked with the risk of lung cancer (Tan et al, 2019). TLR4 is considered an important innate and adaptive immune response molecule against TB.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-4 polymorphisms have been found linked with the risk of lung cancer (Tan et al, 2019). TLR4 is considered an important innate and adaptive immune response molecule against TB.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood (5 mL) from each subject was collected in test tube containing ethylenediamine tetraacetic acid and all blood samples were stored in a refrigerator at −80°C . Then, we extracted DNA from the blood samples using the Gold‐Mag nanoparticles method (Gold Mag Co., Ltd, Xian, China) and measured the DNA concentration and purity with a NanoDrop 2000C (Thermo Scientific, Waltham, MA, USA) …”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood (5 mL) from each subject was collected in test tube containing ethylenediamine tetraacetic acid and all blood samples were stored in a refrigerator at −80 C. 14 Then, we extracted DNA from the blood samples using the Gold-Mag nanoparticles method (Gold Mag Co., Ltd, Xian, China) 15,16 and measured the DNA concentration and purity with a NanoDrop 2000C (Thermo Scientific, Waltham, MA, USA). 17 We selected SNPs of LOC105377871 and CASC16 with the minor allele frequencies > 5% in global population from the 1000 Genome Project (http://www.internationalgenome.org). Furthermore, the genotype distribution of SNPs in the control group was in accordance with Hardy-Weinberg equilibrium (HWE) (p > 0.05).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…But our result was different from Cozar et al [25]; they did not find that the polymorphism of IL-4 rs2243250 was also associated with the susceptibility of renal cell carcinoma. In addition, Pan et al [32] and Tan et al [37] have found that IL-4-590C/T variant was relevant with the increased risk of lung cancer and gastric cancer. The possible reasons for the different results of the above studies have been summarized as follows: (1) the genetic background of the population was different; (2) the sample volume of Asians we included in this meta-analysis was much larger than that of Caucasians; (3) the methods of genotyping were different in these included studies; (4) the different types of smoking-related cancers had different relationships with IL-4 rs2243250 polymorphism.…”
Section: Discussionmentioning
confidence: 99%